Claiming and defending abortion rights in South Africa - Cathi Albertyn (Revista Direito GV)
ABSTRACT The South African transition to democracy enabled successful claims for gender equality and reproductive rights in the Constitution and in law. This article explores that transition with a focus on the enactment of a progressive abortion law; the feminist, rights and public health narratives that justified it; and the manner in which it transformed constitutional and legal norms about women and reproductive choice, despite a broadly conservative society. Then, it discusses twenty years of the Act in practice, highlighting its uneven implementation in the face of significant normative resistance and changing narratives. It also describes the ebb and flow of rights protection in changing social and political conditions, and demonstrates the importance of constitutional and legal guarantees to abortion as a bulwark against their erosion. At the same time, it illustrates the importance of political will, feminist narratives and civil society activism in maintaining effective access to safe, legal abortion for poor, black, working class and rural women.